Leiomioma benigno metastatizante de veia cava inferior: rara complicação tardia de histerectomia - Marcos Filgueiras; Antônio Carlos Barros Lima Jr; Walter Giulliano Baldoni; Washington Sérgio Gonçalves Milezi; Ricardo Zorron (Revista do Colégio Brasileiro de Cirurgiões)
Large vessel tumors diagnosis is usually difficult. Benign metastasizing leiomyoma is a rare condition occurring inside peripheral vessels. There are few publications about this tumor inside inferior vena cava. A 54 years old female patient is presented with a previous hysterectomy for myomas. She complained of no specific symptoms 18 months after surgery. Computer tomography revealed a 7.5 x 3.5 x 4.0 cm mass at inferior vena cava and right psoas muscle. After surgical management and immunohistochemical screening biopsy, the diagnosis was benign metastasizing leiomyoma of inferior vena cava. The patient recovery was uneventful. Benign metastasizing leiomyoma of inferior vena cava is a very rare condition, and must be suspected in patients with primary leiomyosarcoma, especially in women previously submitted to hysterectomy for leiomyomatosis.